FRANCE IN THE ARCTIC: IN SEARCH OF “PLACES UNDER THE SUN” - M. B. Bashkirov; M. E. Antonova (Сравнительная политика, 2020)
The Arctic is not the traditional priority of the French foreign policy, but in recent decades the Arctic has become a ﬁ rm part of country’s national interests. Political experience gained in the Antarctic region gives France grounds to consider itself as a “polar nation” and claim the status of an “Arctic actor”. The key message of the national Arctic strategy “The Great Challenge of the Arctic: national roadmap for the Arctic” of 2016 is an identiﬁ cation of forms of the collaborative governance, that can be appealing for the international community. The closest partner for France in this direction is the European Union. Scenarios of Arctic governance, proposed by non-regional players, are often unacceptable for most Members of the Arctic Council.Presently, it is challenging for France to ﬁ nd new forms of cooperation in the region: France is not among the primary partners for the Arctic states, except for the activities of transnational corporations. Efforts to turn the “subarctic” archipelago Saint-Pierre et Miquelon into a springboard for France’s possible expansion in the Arctic is an unlikely event. Environmental topics play a crucial role in French politics in the circumpolar region. The global nature of environmental issues, especially climate change, is emphasised both in ofﬁ cial documents and in statements of the highest authorities of the Fifth Republic. In the near future, under Emmanuel Macron’s leadership, France intends to become a world leader in the ﬁ ght against global warming. In addition, France's new polar ambassador Ségolène Royal has a vast experience in solving environmental problems and enjoys considerable authority in this ﬁ eld.